Sistem Informasi Rekam Medis Pada Praktek Dokter Hewan Nurcahyo Saksono Berbasis Web - Melda Agharina; Eva Rianti (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2021)
A medical record is a file containing records and documents about the patient's identity, examination, treatment, actions and other services that have been provided to the patient on health care facilities. The problems that occur in the veterinarian Nurcahyo Saksono is the management of medical data that is less effective and efficient. The development method with Prototype method, while the program was built using PHP, MySQL and Bootstrap. The results of the medical record information system in the practice of Nurcahyo Saksono Veterinary web- based can facilitate the search for data, examination documents, patient data, medical record data or report data per period because it is integrated and stored into a database and can be accessed anywhere or anytime . With a web-based medical record information system about Nurcahyo Saksono's Veterinarian practices, he can speed up the administration process in terms of registering medical records, scheduling practices, and consulting pet owners that can be online without having to come. Keywords: Medical Record Information System; Veterinarian; Prototype; Website.